Cristais do neurotransmissor gaba, do ácido oxálico e seu co-cristal: crescimento, medidas e cálculos DFT de suas propriedades. - Silva, José Barbosa da (2020)
Gamma-aminobutyric acid, or γ-aminobutyric acid, is the main inhibitory neurotransmitter in the central nervous system of a developing mature mammal. Its main role is to reduce neuronal excitability throughout the nervous system. GABA is sold as a dietary supplement. In 1883, GABA was first synthesized and was known only as a metabolic product of plants and microbes. GABA is synthesized mainly from glutamate through the enzyme glutamate decarboxylase (GAD) with pyridoxal phosphate (the active form of vitamin B6) as a cofactor. This process converts glutamate (the main excitatory neurotransmitter) into GABA (the main inhibitory neurotransmitter). Many studies on GABA are being developed all over the world. In this work, the crystallization of commercial GABA alone and a cofactor, in this case oxalic acid, were carried out in the formation process of the GABA-OXA co-crystal, aiming at the improvement physicochemical properties, especially solubility, and quantum calculations were also performed via DFT. For an in-depth understanding of the experimental data, we calculate the structural, electronic, optical and vibrational properties (including phonons and thermodynamic properties) of GABA, oxalic acid and co-crystal of their monolayers and isolated molecules in the context of the Density Functional Theory (DFT). As main results we obtained that: the energy gap for GABA is in excellent agreement with the indirect gap that we obtained from the DFT calculation; the vibrational frequencies of the GABA calculated via DFT are reported for the first time. Atomic movements were assigned to each of the modes, and vibrational signatures for GABA were identified. Functional density calculations were performed to study the solid / state properties of the two monoclinic-tetragonal GABA polymorphs and the monohydrate and hexagonal crystals. Unit cell geometries have been optimized, Kohn-Sham electronic energy bands, electronic state densities, population loads, optical absorption and complex dielectric functions have been obtained for each GABA system using a GGA functional plus TS dispersion correction, leading to network parameters very close to the experimental values. The structures of fundamental theoretical bands of all GABA crystals are direct except the monoclinic (indirect) with energy gap close to 5 eV. Optical absorption and dielectric function are very sensitive to the polarization of light in all GABA crystals.